Perlindungan hukum dalam pelayanan rawat inap peserta BPJS mandiri sebagai bagian layanan publik kesehatan - Yofiza Media; Leonardus Davinci Siboro (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Health services constitute a constitutional right of every citizen, including self-funded BPJS Kesehatan participants who receive inpatient care in hospitals. In practice, however, various obstacles remain that may create gaps between legal norms and their implementation, as observed at RSUD dr. Rasidin Padang. This study aims to analyze the implementation of inpatient services for self-funded BPJS Kesehatan participants, identify the obstacles encountered, and examine the hospital’s responsibilities and efforts in providing legal protection for patients. The research employs a sociological juridical approach using an empirical legal research method. Data were collected through interviews with hospital management, healthcare personnel, and patients, as well as through a literature review of relevant laws and regulations. The findings indicate that inpatient services are generally implemented in accordance with applicable legal provisions; nevertheless, constraints such as limited inpatient capacity, service waiting times, and the complexity of BPJS administrative procedures persist. Therefore, hospitals bear the responsibility to deliver safe, high-quality, and non-discriminatory services and to continuously improve service mechanisms to ensure the protection of the rights of self-funded BPJS Kesehatan patients.